((1/3a)-3)((1/3a)-3)

Simple and best practice solution for ((1/3a)-3)((1/3a)-3) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for ((1/3a)-3)((1/3a)-3) equation:


a in (-oo:+oo)

((1/3)*a-3)*((1/3)*a-3) = 0

(1/3*a-3)^2 = 0

1/3*a-3 = 0 // + 3

1/3*a = 3 // : 1/3

a = 3/1/3

a = 9

a in { 9, 9 }

See similar equations:

| n^2-7=6n | | ((1/3a)-3)^2 | | 3606=2x+x | | 12x+12-4x+4=40 | | b^2+30=11b | | X/8=76 | | 0.5(0.26+9x)=5.2x | | p^2-8p=-7 | | y=-5x^3-5x^2+60x | | 4/5g=1/4 | | mx/9=9 | | n^2=6-n | | -2.4x/-1.5= | | 5/7z=2/3 | | 13=x+13 | | 47=5w+12 | | 5(x+1)=2+x | | -382+9x=54x-23 | | x+y+z+a=12.68 | | 7x=-5x+2 | | 9883640/x=100/-0.6 | | 9883640/x=100-0.6 | | (1-x^3)(dy/dx))=3x^y | | -4=6+w | | -8x-2=10x-38 | | 3p=p+34 | | -x+6=-2x-32 | | 42u=252 | | f(x)=cotg(3-2x) | | 3q+6=q+14 | | 26=6x-8 | | 6y-14=16whatisy |

Equations solver categories